Psychedelic Mushrooms in the USA: Knowledge, Patterns of Use, and Association With Health Outcomes - Matzopoulos, Richard; Morlock, Robert; Morlock, Amy; Lerer, Bernard; Lerer, Leonard (Frontiers in Psychiatry, 2022)
Introduction: Popular media coverage of psychedelics use, growing research into this class of compounds for psychiatry and decriminalization initiatives, are transforming the public perception of psychedelics. However, little is known about levels of knowledge and psychedelic mushroom (PM) use among American adults. Methods: We examined PM use and various measures of health status, quality of life and self-reported mental health outcome measures obtained through a national on-line, cross-sectional survey of adults with a demographic composition representative of the US adult population by region, gender, age, and race (weighted N = 251,297,495) from November 2020–March 2021. Results: General mental health and well-being were popular reasons for PM use (63.6%), although use for medically-diagnosed (31.8%) and self-diagnosed (19.0%) conditions was also common. PM users reported more depression and anxiety as reflected in higher GAD-7 and PHQ-9 scores. Factors predictive of PM use included being male [OR 1.54 95% CI 1.09-2.15] and having higher Charlson Comorbidity Index scores [OR 1.42; 95% CI 1.22-1.65]. Self-reported PM use was less likely among participants with health insurance [OR=0.50 (0.35-0.72)], increased age [OR=0.92 (0.90-0.93)] and, relative to those living in the west US census region, living in the northeast [OR=0.27 (0.15-0.50)], midwest [OR=0.34 (0.20-0.56)], and south [OR=0.38 (0.26-0.55)]. Conclusions: A significant number of Americans are already “self medicating” with PM and as growing positive media coverage of psychedelics drives public interest in the health benefits of PM, this number will increase. The association between PM use and poor mental health requires further research to inform policy.